E-LKPD Inkuiri Berbantuan Wizer.Me: Solusi Dalam Mengasah Kemampuan Analitis Siswa Kelas V - Imanuel Herlimus Leba; Toto Nusantara; Candra Utama (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study was conducted to improve the analytical thinking skills of fifth-grade students at SD GMIT 7 Oebufu in Kupang City through the implementation of inquiry-based E-LKPD designed using the Wizer.Me platform. The study used a quantitative method with a quasi-experimental pre-test post-test design. The research subjects were 26 fifth-grade students in the experimental class and 27 fifth-grade students in the control class, who received different treatments. The experimental class used a different learning approach than the control class, which employed conventional inquiry-based worksheets. The instruments used Bloom's taxonomy indicators to assess students' analytical thinking skills through pre-tests and post-tests. Meanwhile, an observation sheet was used to monitor the learning process during the inquiry stages. The analysis results showed that in the experimental class, the average analytical thinking ability score increased from 56.25 to 81.7, while in the control class, it increased from 56.18 to 75.46. Additionally, the N-Gain test showed moderate effectiveness in both classes, but the experimental class achieved a higher percentage increase, 52.18%, compared to 39.63% in the control class. Although there was no significant difference in the results of the independent sample t-test (p = 0.124), the data still showed that the use of inquiry-based E-LKPD yielded higher results in improving analytical thinking skills. Thus, the implementation of inquiry-based E-LKPD through Wizer.Me is considered an effective and relevant learning strategy in meeting the demands of the 21st century.